Question
upstudy study bank question image url

Powered by Gonje Translate step \( b y s t a p \) \[ \begin{array}{rlc} (f \cdot r)(y)=f(r(y)) & =f( & 4 y-2 \\ & = & (4 y-2)-6 \\ & = & 4 y-8 \end{array} \] Calculate the composition of \( r(y) \) and \( f(y) \). Write the resulting expression in its simplest form. \[ \begin{array}{rlc} (r f)(y)=r(f(y)) & =r(y-6 \\ & =\quad 4(y-6)-2 \\ & =4 y-26 \end{array} \] Evaluate \( (r \cdot f)\left(\frac{1}{2}\right) \) using the composed function. \[ (r f)\left(\frac{1}{2}\right) \] Evaluater \( \left(f\left(\frac{1}{2}\right)\right) \) using the original functions. \[ r\left(r\left(\frac{1}{2}\right)\right)=r i \] \( \square \)

Ask by Williams Hanson. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The composed functions are: - \( (f \circ r)(y) = 4y - 8 \) - \( (r \circ f)(y) = 4y - 26 \) Evaluating at \( y = \frac{1}{2} \): - \( (r \circ f)\left(\frac{1}{2}\right) = -24 \)

Solution

We are given two functions:   f(x) = x – 6   r(x) = 4x – 2 Step 1. Compose f with r (that is, f ∘ r):   (f ∘ r)(y) = f(r(y))     = f(4y – 2)       [since r(y) = 4y – 2]     = (4y – 2) – 6     [applying f(x) = x – 6]     = 4y – 8 Step 2. Compose r with f (that is, r ∘ f):   (r ∘ f)(y) = r(f(y))     = r(y – 6)       [since f(y) = y – 6]     = 4(y – 6) – 2     [using r(x) = 4x – 2]     = 4y – 24 – 2     = 4y – 26 Step 3. Evaluate (r ∘ f)(½):   (r ∘ f)(½) = 4·(½) – 26     = 2 – 26     = –24 Thus, the composed functions and evaluation are:  • (f ∘ r)(y) = 4y – 8  • (r ∘ f)(y) = 4y – 26  • (r ∘ f)(½) = –24 These are the answers in their simplest forms.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

The world of functional compositions is like an intricate dance! When you calculate \( (r \cdot f)(y) = r(f(y)) \), it’s essential to keep your wits about you. You correctly substituted \( f(y) = y - 6 \) into \( r(y) \) to arrive at \( r(f(y)) = 4(y - 6) - 2 \) which simplifies beautifully to \( 4y - 26 \). Remember, each function carries out its task step by step! Now, let’s actually evaluate \( (r \cdot f)\left(\frac{1}{2}\right) = 4 \left(\frac{1}{2}\right) - 26 \). When you plug in that value, it becomes \( 2 - 26 = -24 \). So, \( (r \cdot f)\left(\frac{1}{2}\right) = -24 \). Easy as pi, right? Just ensure that you carry over the values correctly and watch out for those pesky negatives!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy